Expanding the Immunophenotypic Spectrum of Neoplastic and Reactive Plasmacytoid Dendritic Cells. Issue 5 (6th March 2023) - Wu, Sarah J; Sadigh, Sam; Lane, Andrew A; Pinkus, Geraldine S
Abstract: Objectives: Targeted therapies for blastic plasmacytoid dendritic cell neoplasm (BPDCN) have presented a diagnostic dilemma for differentiating residual BPDCN from reactive plasmacytoid dendritic cells (pDCs) because these conditions have a similar immunoprofile, necessitating discovery of additional diagnostic markers. Methods: Fifty cases of BPDCN involving bone marrow (26/50) and skin (24/50) as well as other hematologic malignancies (67) and nonneoplastic samples (37) were included. Slides were stained using a double-staining protocol for the following immunohistochemical marker combinations: TCF4/CD123, TCF4/CD56, SOX4/CD123, and IRF8/CD123. Results: The nuclear marker SOX4 is expressed in neoplastic pDCs; in our cohort, SOX4/CD123 showed 100% sensitivity and 98% specificity in distinguishing BPDCN from reactive pDCs and other neoplasms. TCF4/CD56 had a 96% sensitivity and 100% specificity for BPDCN. IRF8 is a nonspecific marker that is positive in BPDCN and pDCs as well as other myeloid malignancies. Conclusions: The novel immunohistochemical combination SOX4/CD123 distinguishes BPDCN, including CD56-negative BPDCN, from both reactive pDCs and other neoplasms. Because of their high diagnostic sensitivity and specificity, the double-staining marker combinations TCF4/CD123, TCF4/CD56, and SOX4/CD123 can be used to confirm lineage in BPDCN cases and detect minimal/measurable residual disease in tissue specimens.